Bimbingan Konseling Islam (Bki) Mendukung Pengasuh Langsia Demensia - Wannadwah Binte Ja’afar (Counseling As Syamil Jurnal Ilmiah Bimbingan Konseling Islam, 2026)
The increasing number of elderly people with dementia has placed a great responsibility on caregivers and family members. Family members play a very important role and need to be sensitive to the atmosphere that will change mental health, emotions, role conflicts, and experiencing crises in life. Therefore, this study aims to explore and discuss the role and contribution of Islamic Counseling Guidance (BKI) as a support approach for caregivers and patients. It also uses a collaborative approach and integration between techniques or assessments from western psychology in order to strengthen and provide benefits to caregivers and patients. This study also suggests that the BKI approach be applied more systematically in counseling approaches.